High content corn starch/Poly (butylene adipate-co-terephthalate) composites with high-performance by physical–chemical dual compatibilization. (5th October 2021) - Li, Chengqiang; Chen, Fangping; Lin, Bowen; Zhang, Chenhao; Liu, Changsheng
Graphical abstract: Highlights: Starch/PBAT composites with high starch content were successfully prepared by in-situ melt blending reaction. Starch/PBAT composites possessed excellent mechanical properties via physical–chemical dual compatibilization. UP and MDI effectively improved the thermal stability and water resistance of Starch/PBAT blends. MDI content was a key influencing factor on performance of the composites. Abstract: The corn starch/Poly (butylene adipate-co-terephthalate) (PBAT) composites with high starch content and high mechanical strength were prepared by in-situ reaction with 4, 4′-methylene diphenyl diisocyanate (MDI) as bifunctional crosslinker and polyurethane prepolymer (PUP) as starch modifier and physical compatibilizer. We studied the effects of different MDI contents on the mechanical properties, morphology, thermodynamics, rheology, water absorption and heat-sealing properties of starch/PBAT composites. The results showed that MDI was an effective reactive crosslinker, promoting the interfacial adhesion between modified starch and PBAT. The hydrophobicity, thermal stability, heat-sealing performance and mechanical properties of Starch/PBAT composites enhanced with the increased contents of MDI. The tensile strength and elongation at break of composites with 60% starch content reached 10.95 MPa and 461.23 %. The potent interfacial compatibility of starch/PBAT composites was mainly attributed to the chemical cross-linking of MDI and the physical compatibilization of PUP. Physical-chemical dual compatibilization in our study provided an effective strategy for preparing biomass-based polymers.